KEPEMIMPINAN KEPALA MADRASAH DALAM MENINGKATKAN KINERJA GURU PADA MAN MODEL BANDA ACEH - Yusnidar Yusnidar (Universitas Islam Negeri Ar-Raniry, 2014)
School head master is one of factors in encouraging the school to reach its vision, mission, aim and target through the planned implemented program. The aim of the study is to know the leadership of the head master of the school in improving the teachers’ commitment, work motivation and obstacles experiencing by the school head master in improving the teachers’ performance at MAN Model Banda Aceh. The study used descriptive method. The data collection techniques were observations, interviews, and documentations. The subjects of this research were the head master of the school and the teachers of MAN Model Banda Aceh. The data analysis of this qualitative analysis shows that: (1) the leadership of the head master of the school in improving working commitment is through empowerment of the training teacher in accordance with their field, class supervision evaluation and interns routinely madrasah supervision, and give reward to outstanding teacher; ( 2 ) the school head master leadership in improving work motivation is through professionalism work guiding, evaluate the teacher learning program, consensus agreement in time discipline, and intern cooperation with the school head master and guiding teachers; (3) the head master leadership in improving discipline is through applying self discipline of school head master in order to be followed by teachers as the discipline being conducted by the school head master in fully self awareness without any coercion; (4) the obstacles faced by the school head master in improving the teacher performance is because of time restriction in carrying out classroom supervision, guiding professional teachers and evaluate the teachers teaching-learning process, as well as restricted fund allocation in MAN Model Banda Aceh.